2022
DOI: 10.1590/0074-02760220200
|View full text |Cite
|
Sign up to set email alerts
|

Family Herpesviridae and neuroinfections: current status and research in progress

Abstract: This article addresses the relationship between human herpesviruses (HHVs) and neuroinfections. Alphaherpesviruses, betaherpesviruses and gammaherpesviruses are neurotropic viruses that establish latency and exhibit reactivation capacity. Encephalitis and meningitis are common in cases of HHV. The condition promoted by HHV infection is a purported trigger for certain neurodegenerative diseases. Ongoing studies have identified an association between HSV-1 and the occurrence of Alzheimer's disease, multiple scle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…Among HHVs, the most well-known HSV can infect neurons and reach the CNS through retrograde axonal transport, ultimately leading to diseases such as encephalomyelitis, and several studies have shown that HSV is closely related to NDDs ( Carneiro et al, 2022 ). Primary infection with VZV causes varicella and can latently infect neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Among HHVs, the most well-known HSV can infect neurons and reach the CNS through retrograde axonal transport, ultimately leading to diseases such as encephalomyelitis, and several studies have shown that HSV is closely related to NDDs ( Carneiro et al, 2022 ). Primary infection with VZV causes varicella and can latently infect neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Among the nine herpesviruses, eight are considered neurotropic and are associated with different neurological outcomes [135], except for KSHV, which has not been studied in detail in the context of neurological diseases. Alphaherpesviruses can infect neurons and establish latency.…”
Section: Neurological Disorders Caused By Herpesviruses and Their Ass...mentioning
confidence: 99%
“…Passage across the blood-brain barrier is believed to be mediated by monocytes [143]. Betaherpesviruses can trigger encephalitis, neurodevelopmental deficits, meningoencephalitis, dizziness, and epilepsy [135]. Gammaherpesviruses predominantly establish latency in B cells [144].…”
Section: Neurological Disorders Caused By Herpesviruses and Their Ass...mentioning
confidence: 99%
See 2 more Smart Citations